Desa Tangguh Bencana di Lereng Merapi: Kearifan Lokal dan Modal Sosial Masyarakat Glagaharjo - Fatimahsyam (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This article aims to identify and describe the role of social capital as a resource in enhancing the capacity and self-reliance of the Glagaharjo community in managing the volcanic eruption disasters of Mount Merapi. A qualitative approach was employed, utilizing non-probability sampling and Purposive Sampling for informant selection. Data collection involved interviews, observations, and documentation. The research results indicate that the Glagaharjo Village possesses a culture of mutual cooperation, knowledge of